Non‐isolated buck–boost dc–dc converter with quadratic voltage gain ratio. Issue 6 (1st May 2019) - Gorji, Saman A.; Mostaan, Ali; Tran My, Hung; Ektesabi, Mehran
Abstract : A new transformer‐less buck–boost converter is proposed, which owns a quadratic voltage gain ratio. The proposed converter (a) has only one active switch, which makes the implementation of the gate driver and control system simpler; (b) has a quadratic voltage gain without using a transformer, which equips the designers to obtain a high‐voltage gain ratio and avoid the complexity of magnetic utilisations; (c) works both in step‐up or step‐down mode, while most of the existing quadratic topologies are able to work either in step‐up or step‐down mode; and (d) shares a common ground between the input and output terminals. The operating states of the proposed converter along with its steady‐state performance are analysed. Then, the small‐signal modelling and the power loss analysis are performed. A comparison shows the unique features of the converter, specifically in terms of voltage gain ratio and the count of power switches. Finally, the experimental results of a laboratory prototype, as well as the simulation results from PSIM software, are used for validation. The converter was tested in different conditions to inspect its transient response and to record its efficiency. The maximum recorded efficiencies in boost and buck modes, respectively were 94.7 and 93%.